1983
DOI: 10.1128/iai.39.2.721-725.1983
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutination and adhesiveness of epidemiologically distinct strains of Vibrio parahaemolyticus

Abstract: Twelve strains of Vibrio parahaemolyticus from four epidemiologically distinct groups were examined for their ability to hemagglutinate human, bovine, chicken, guinea pig, and rabbit erythrocytes and to adhere to human buccal mucosal epithelial cells in the presence and absence of mannose. Four of six Kanagawa-positive but none of six Kanagawa-negative strains showed mannose-sensitive hemagglutination with erythrocytes of rabbits and of one or more additional species. Mannose-resistant hemagglutination was sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, colonization of the intestine by V. parahaemolyticus has never been reported, as far as we know. Several investigators have studied the property of V. parahaemolyticus adhesion to cultured tissue cells or chitin (3,4,10,15,20,28), and they dicussed the possibilities that the adherence is mediated by lateral flagella, the outer membrane, or capsular antigen, without mentioning pili (3)(4)(5). Recently, we and Honda et al found pili on the cell surface of V. parahaemolyticus (11,22), and we purified them (22).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, colonization of the intestine by V. parahaemolyticus has never been reported, as far as we know. Several investigators have studied the property of V. parahaemolyticus adhesion to cultured tissue cells or chitin (3,4,10,15,20,28), and they dicussed the possibilities that the adherence is mediated by lateral flagella, the outer membrane, or capsular antigen, without mentioning pili (3)(4)(5). Recently, we and Honda et al found pili on the cell surface of V. parahaemolyticus (11,22), and we purified them (22).…”
Section: Discussionmentioning
confidence: 97%
“…Whether Ha7 pili were monovalently adhesive to erythrocytes was determined by mixing pili and erythrocytes, but no adsorption was seen. Although most adhesive pili and other colonization factors agglutinate erythrocytes (6)(7)(8)27), colonization factors without hemagglutinating activity have occasionally been reported (12,28,32). Honda et al reported a new colonization factor isolated from enterotoxigenic E. coli which had no hemagglutinating activity (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of other attachment structures such as adhesins (45,92), some of which mediate the agglutination of erythrocytes, is far less clear since these molecules are found in a broad range of V. cholerae serotypes originating from diverse sources (18) and fail to show a distinct association with the infectious process (5). In V. parahaemolyticus, adherence has been linked to the possession of a flagellum and hemagglutinins in Kanagawa-positive isolates (128,158); other studies, however, have not shown such a clear correlation (79).…”
Section: Pathogenicity and Virulence Characteristicsmentioning
confidence: 99%
“…Despite many attempts (Brown et al, 1977;Honda et al 1967a;Brown, 1973, 1974) no satisfactory evidence for a filterable enterotoxin has been found. Reports of the organism's invasive (Boutin et al, 1979) and adhesive potential (Carruthers, 1977;Gingras and Howard, 1980;lijima et al, 1981;Reyes et al, 1983) sustantiate the theory that Kanagawa hemolysin is the primary virulence factor. Each sample was inoculated by thorough blending with a culture of V. parahaernolwicus grown 24 hr at 35°C in brain heart infusion (BHI, BBL) broth with 3% NaCl.…”
Section: Introductionmentioning
confidence: 99%